Report of the Working Group on Crop Husbandry, Demand and Supply Projections and Agricultural inputs for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, Government of India, 2001)
The Report of the Working Group on Crop Husbandry, Demand and Supply Projections, and Agricultural Inputs for the Tenth Five Year Plan (2002–2007) provides a detailed assessment of India’s agricultural production scenario, input availability, and future projections to support self-sufficiency and sustainable growth. Constituted by the Planning Commission under the chairmanship of Shri K. Rajan, the Working Group reviewed ongoing schemes of the Department of Agriculture & Cooperation (DAC), evaluating their impact on productivity and input use, while identifying constraints and opportunities for improvement. The report highlights the historical evolution of Indian agriculture, emphasizing the transformative role of high yielding varieties, irrigation, rural infrastructure, and research innovations from ICAR and State Agricultural Universities during the Green Revolution, which led to significant gains in foodgrain production, oilseeds, sugarcane, fruits, and vegetables. Despite these achievements, the 1990s witnessed a deceleration in growth rates of crop production and productivity compared to the 1980s, with foodgrain growth slowing markedly. The Working Group also addressed the availability and efficient use of critical inputs such as seeds, fertilizers, water, farm machinery, and bio-pesticides, and recommended integrated approaches including Integrated Nutrient Management (INM) and enhanced mechanization. Sub-groups focused on demand and supply projections and agricultural inputs to ensure that the production of foodgrains, pulses, oilseeds, and commercial crops meets domestic needs and export potential. The report emphasizes the need for coordinated planning, technology transfer, and targeted programs to improve input efficiency, prevent over-exploitation of natural resources, and sustain productivity growth while maintaining self-sufficiency and supporting rural livelihoods.
Government of India Planning Commission December 2001
Keywords: Crop Husbandry; Demand and Supply Projections; Agricultural Inputs; Foodgrains Production; Green Revolution; High Yielding Varieties; Irrigation; Fertilizer Use; Farm Mechanization; Integrated Nutrient Management; Productivity Growth; Self-Sufficiency